ANALISIS KESALAHAN SINTAKSIS DALAM BERITA DARING KOMPAS.COM MARET 2024 - Siti Fatimah; Nurul Adhimatur Rahmah; Icha Fadhilasari; Arisni Kholifatu Amalia Shofiani (Jurnal PENEROKA, 2024)
The purpose of this research is to analyze several linguistic errors listed in online news from the official Kompas.com account. In writing online news, there are often errors in both punctuation and language structure. News writing must be in accordance with linguistic rules so as not to harm the reader's understanding of the news that has been published. This research utilizes a method that is descriptive qualitative. The data collection applied is the listening and recording technique which is then divided into four stages, namely recording, identifying, classifying and correcting errors. The findings of this research are several Indonesian language errors in the field of syntax including (1) errors in the use of inappropriate sentence patterns, (2) conjunction errors, (3) punctuation errors contained in the official Kompas.com account.